Spatial-based analysis for risk erosion hazard in Jordan - Doaa Abuhamoor; Lubna AlMahasneh; Abdel Razzaq Al Tawaha (Universitas Sebelas Maret, 2025)
Soil erosion is a critical environmental issue in Jordan, particularly due to the country’s fragile ecosystems, steep slopes, and varying climatic conditions. It poses significant threats to agricultural productivity, natural resource conservation, and land sustainability. This study aims to provide a detailed spatial assessment of soil erosion risk across Jordan and identify erosion-prone zones to support informed decision-making in land management. The Revised Universal Soil Loss Equation (RUSLE) model, integrated with Geographic Information System (GIS) tools, was employed to estimate soil loss and map erosion severity. The model incorporated essential factors including rainfall erosivity, soil erodibility, slope length and steepness, vegetation cover, and conservation practices. Erosion rates were categorized into three classes: low (0–10 tons ha-1 year-1), moderate (10–50 tons ha-1 year-1), and high (>50 tons ha-1 year-1). Results revealed that 94% of Jordan’s land is subject to low erosion risk, 5% to moderate risk, and approximately 1% to high risk. The areas most vulnerable to erosion are located in the northern and central highlands and parts of the Jordan Valley, primarily due to their steep topography and higher precipitation levels. This study demonstrates the effectiveness of integrating RUSLE with GIS to identify critical erosion hotspots and inform targeted soil conservation strategies, contributing to more sustainable land use planning in arid and semi-arid regions like Jordan.